2015
DOI: 10.1038/srep10847
|View full text |Cite
|
Sign up to set email alerts
|

Trans-generational responses to low pH depend on parental gender in a calcifying tubeworm

Abstract: The uptake of anthropogenic CO2 emissions by oceans has started decreasing pH and carbonate ion concentrations of seawater, a process called ocean acidification (OA). Occurring over centuries and many generations, evolutionary adaptation and epigenetic transfer will change species responses to OA over time. Trans-generational responses, via genetic selection or trans-generational phenotypic plasticity, differ depending on species and exposure time as well as differences between individuals such as gender. Male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…For instance, Donelson, Munday, McCormick, and Pitcher (2012) found that damselfish ( Acanthochromis polyacanthus ) exposed to thermal stress produce offspring with superior thermal tolerance relative to offspring of unexposed parents. Other studies, however, have shown that stressful parental environments can lower offspring quality (Guillaume, Monro, & Marshall, 2016; Huxman et al., 1998; Lane, Campanati, Dupont, & Thiyagarajan, 2015; Shama & Wegner, 2014). In our study, maternal environmental effects on survival were unlikely to have been caused by past environmental conditions, as all mothers came from the same collection site and were acclimatized before use.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Donelson, Munday, McCormick, and Pitcher (2012) found that damselfish ( Acanthochromis polyacanthus ) exposed to thermal stress produce offspring with superior thermal tolerance relative to offspring of unexposed parents. Other studies, however, have shown that stressful parental environments can lower offspring quality (Guillaume, Monro, & Marshall, 2016; Huxman et al., 1998; Lane, Campanati, Dupont, & Thiyagarajan, 2015; Shama & Wegner, 2014). In our study, maternal environmental effects on survival were unlikely to have been caused by past environmental conditions, as all mothers came from the same collection site and were acclimatized before use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, parental exposure to ocean acidification increases the rate of juvenile development in the Sydney rock oyster, Saccostrea glomerata (Parker et al, 2012), but decreases developmental rate in G. aculeatus (Schade et al, 2014). The relationship is further complicated in the marine tubeworm Hydroides elegans, whose offspring grow twice as fast if the fathers have been exposed to ocean acidification but 25% slower if the mothers experience the same conditions (Lane et al, 2015). As both the males and females were exposed to ocean acidification in this study, it is possible that the neutral response that we observed in F2, F4 and F6 are driven by opposite, additive effects of the parental environment experienced.…”
Section: −1mentioning
confidence: 97%
“…Several transgenerational studies have measured the effect of ocean acidification on juvenile development (Parker et al, 2012;Schade et al, 2014;Lane et al, 2015), but no pattern is evident in the results. For example, parental exposure to ocean acidification increases the rate of juvenile development in the Sydney rock oyster, Saccostrea glomerata (Parker et al, 2012), but decreases developmental rate in G. aculeatus (Schade et al, 2014).…”
Section: −1mentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite recent evidence that many physiological, behavioural, immunological, molecular and neuro-toxicological functions are influenced by sex-based differences [9,10], and despite many of these same processes being impacted by elevated pCO 2 [5], the overarching role of sex in determining response to OA remains understudied [11]. Here, we employ a systematic map approach: a transparent, robust and repeatable method to identify and collect relevant literature to answer the question of how sex is considered within experimental OA research [12].…”
Section: Introductionmentioning
confidence: 99%